(untitled) (Al-Aasar, 2025)
This paper examines the concept of war preparation in the context of the Noble Quran and the Seerah of the Messenger Salla Allahi alaih wasallam, as well as its contemporary applications. It is obivious that the Islamic Government and Muslims require the defence of the Islamic state, and any negligence in this regard is not permissible and can cause a great loss. So the research question of this paper is: What is the Quranic and Prophetic viewpoint of war preparation? And what are its contemporary applications? In the Holy Quran, it is said clearly to be prepared for war; the Messenger SAW also explained and implemented it. The Holy Quran stresses the preparation of powerful and trained horses. The Prophet said Power means shooting. The Exegetes of the early modern and contemporary era interpret this ayah keeping in view the current situation and modern technology of war. According to their interpretation, power, each and every thing required in war, and trained horses denote all kinds of military. Muslims and Islamic States must achieve advancement in war technology, new equipment, and weapons. They said that the Islamic state should prepare for war against enemies according to the time and location, and it should be according to their capacity; it is not necessary to be equal with them in quantity and quality. The objective of this research is to clarify the Qur’ānic and Prophetic viewpoint on war preparation and to know about its contemporary applications. The methodology of this research is descriptive analysis.